Guillain-Barré syndrome in Denmark: validation of diagnostic codes and a population-based nationwide study of the incidence in a 30-year period - Levison, Lotte Sahin (Clin Epidemiol, 2019)
Purpose: To validate the diagnostic codes for Guillain-Barré syndrome (GBS) in the Danish National Patient Registry (DNPR). Secondly, to examine 30-year trends in the incidence of GBS in Denmark. Patients and methods: We used the DNPR to identify all patients aged 16 and above diagnosed with a primary GBS diagnosis at any Danish department of neurology between 1987 and 2016. Medical files were reviewed according to the clinical criteria of the National Institute of Neurological Disorders and Stroke Committee and classified according to the Brighton criteria. The incidence rate (IR) was calculated based on data from 1987 to 2016 and stratified by season, gender, and age. Results: Over 30 years, we identified 2,319 patients aged 16 and above in the DNPR. From a validation cohort of 573 patients, we were able to retrieve 425 (74.2%) medical files; 356 GBS diagnoses were confirmed. The overall positive predictive value was 83.8% (95% confidence interval (CI): 80.0–87.0). In 99% of the confirmed patients, the Brighton criteria level 1–3 for GBS were met. The IR was fairly stable over 30 years at 1.77 per 100,000 person years (95% CI: 1.70–1.84). The incidence was higher in the winter season (IR ratio compared with summer: 1.18 (95% CI: 1.09–1.29)), and was strongly associated with male gender (IR ratio vs females: 1.44 (95% CI: 1.33–1.57)). IRs rose with age at diagnosis, particularly after the age of 50 in both men and women and a minor peak was observed for total IR in young adults. Conclusion: Primary diagnostic codes for GBS at Danish departments of neurology have high validity. The DNPR is a well-suited data source for epidemiological research on GBS. The Danish nationwide 30-year GBS IR is stable over time and similar to GBS IRs reported in other European and North American populations.